Energy Transformation of the EU Defense Industry : A Study of France - Hafda Prima Agung; Nugrahani, Henny Saptatia Drajati (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the challenges of energy transformation in the EU Defense Industry, particularly those carried out by French. The French defense industry is adapting its operation to the EU’s new energy policy, which include investment in green technologies, sustainable supply chain management, and adaptation to increasingly stringent environmental regulations. The energy transformation strategy in the French defense industry is important to explore because France is one of the major players in the global defense industry. The research method used is qualitative method with data is obtained through in-depth interviews, policy analysis, and case studies to understand the context, perceptions, and experiences of key actors related to policy implementation. This research uses Daniel Yergin’s energy security theory to analyze the relationship between energy and security and the challenges faced in global energy transformation. In addition, this study uses the energy policy theory of Amory B. Lovins, to analyze, evaluate and implement energy transformation policies. Lovins, to analyze, evaluate and provide recommendations regarding energy transformation strategies in the context of the French defense industry. The study’s findings is that the European Union has established an environmentally friendly strategi yon defense industry and France as one of the member states has implemented the practice in its national security defense operations. The conclusion the study is that EU energy policy has encouraged energy transformation in the French defense industry without undermining France’s national defense progress